Influence of post design and elastic modulus mismatch between dentin and post-core on stress distribution in endodontically treated teeth: a finite element analysis study - Sirigam, Sharmista Reddy; Karnatam, Dinakar; Reddy, Upendra Natha; Neshaneni, Sathish Kumar; Yalamanchi, Anusha; Sri, Satyavathi (International Journal of Dental Materials, 2024)
Background: ParaPost Fiber Posts are made to use resin-based cement and core build-up materials to provide an optimal Monoblock between the dentin-post-crown, resulting in one cohesive restoration. Aim: To evaluate the stress distribution pattern of a Severely damaged maxillary central incisor restored with ParaPost Taper lux, fiber lux and E-max crown using Finite element analysis. Materials and methods: Two 3-D FEA models of maxillary central incisor were simulated with anatomy-based geometric structures. Different Glass Fiber reinforced composite posts (PTL and PFL) and full coverage restorations (Lithium disilicate) were used. The paracore (dual-cured glass-reinforced composite material) was used for core build-up and cementation of both the Posts and full coronal restorations to create an optimal Monoblock effect. MODEL 1: Parapost Taper Lux (PTL), Paracore & Lithium disilicate Full coverage restoration. (LidiS). MODEL 2: Parapost Fiber Lux (PFL), Paracore & Lithium disilicate Full coverage restoration. (LidiS). A 3D model of the maxillary central incisor area, including restorative components, was created. The normal masticatory load of 100 N were applied at a 5mm distance from the incisal edge, at an angle of 45? in relation to the long axis of the tooth was simulated onto the imported models. Von Mises [Vm] stresses generated at the Post–Core assembly, Coronal & Radicular dentin were numerically recorded, color-coded, and compared. Results: The maximum stresses were evidenced both at the mid and coronal thirds of the labial aspects of radicular dentin, and the least stresses were observed at the palatal aspect of apical 3rd. Conclusion: Parallel-sided post (Parapost Fiber Lux) showed the greatest stress distribution on the middle third of the labial radicular dentin.